Clinical outcomes of single‐site laparoscopic interval appendectomy for severe complicated appendicitis: Comparison to conventional emergency appendectomy. Issue 5 (17th July 2019) - Miyo, Masaaki; Urabe, Shoichiro; Hyuga, Satoshi; Nakagawa, Tomo; Michiura, Toshiya; Hayashi, Nobuyasu; Yamabe, Kazuo
Abstract: Aim: Single‐site laparoscopic interval appendectomy (SLIA) for severe complicated appendicitis after conservative treatment (CT) to ameliorate inflammation and eradicate the abscess should be safer and less invasive than emergency appendectomy (EA). However, only a few reports have been published regarding SLIA. Methods: We retrospectively collected data on 264 consecutive patients admitted to Kinan Hospital for treatment of appendicitis between 2012 and 2018. The safety and feasibility of SLIA and its perioperative outcomes for severe complicated appendicitis were investigated. Results: A total of 61 patients were included in this study, 25 of whom underwent CT and 36 EA. Among the 25 patients who underwent CT, 23 (92.0%) succeeded; a total of 16 patients (69.5%) underwent SLIA. Compared to the EA group, the SLIA group had less bleeding (median volume 8.5 vs 50 mL, P  =   .005) and lower rate of expansion surgery (0% vs 27.8%, P  =   .022). Although the postoperative hospital stay was shorter in the SLIA group than in the EA group (9 vs 12 days, P  =   .008), the total hospital stay, including the CT period, was longer in the SLIA group than in the EA group (24 vs 12 days, P  <   .001). Conclusion: SLIA is safe, feasible, and less invasive than EA and may provide the advantages of minimally invasive surgery even if appendicitis is severe. SLIA may be a promising option for complicated appendicitis in select cases despite its disadvantage of prolonging the hospital stay. Abstract : Single‐site laparoscopic interval appendectomy is safe, feasible, and less invasive than emergency appendectomy and may provide the advantages of minimally invasive surgery even if appendicitis is severe. Single‐site laparoscopic interval appendectomy is a promising option for complicated appendicitis.